Impact of Standard and Low-Pressure Pneumoperitoneum on Intraoperative Complications in Laparoscopic Cholecystectomy - Hassan, Maazul; Naveed, Muhammad; Hasham Ashraf, Muhammad; Ahmad Khan, Rizwan; Khaliq Khan, Fareeha; Ara, Jahan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare LPP and SPP laparoscopic cholecystectomy regarding efficiency and complications Methodology: Sixty patients were enrolled. Patients were divided into two groups. 30 patients were placed in each group A and B. The intensity of postoperative shoulder pain was assessed by using visual analog scale (VAS) at 4,8,12 and 24 hours after surgery. Nausea & vomiting episodes also measured at 4,8,12 and 24 hours after surgery. The length of operation, intra-operative findings, intra-operative complications (bile spilling, visceral injury and hemorrhage), and hospital stay were also noted. Results: Patients in this study were divided into two groups: group A and B. The frequency of shoulder pain at different periods was from 0 to 7 i.e. No pain, Mild, Moderate, and worst which was counted by the minimum to maximum i.e. 2 and 7 at 4 hours, 2 and 9 at 8 hours, 1 and 8 at 12 hours and 0 to 8 at 24 hours. Regarding intra-operative complications i.e. Bile Spillage, bleeding and visceral injury, only a few patients had bouts of nausea/vomiting in the 4 hours and 24 hour time intervals. However, more patients were affected by this condition at 8 and 12-hour intervals. Conclusion: LP laparoscopic surgery is an achievable alternative to SP laparoscopic procedure for benign issues of gall stone. LPP is a better choice for the LC since it minimizes post-operative pain of the shoulder & the PONV while causing no significant increase in intraoperative complications.